Enhancement of mechanical properties in unsaturated polyester via reinforcement with olive leaf particles - Eman Ibraheem; Waleed Bdaiwi (Engineering and Technology Journal)
The use of olive leaf powder (OLP) as a filler material in unsaturated polyester composites brings a new avenue for the development of mechanical and thermal properties. The present work focuses on the impact of the relative proportions of OLP ranging from (0, 5, 10, 15, 20, and 25%) on the structural, electrical, and thermal properties of the composites.The specimens were prepared through the hand lay molding process, and the hardness strength, impact strength as well as compressive strength examination were conducted.These findings suggest that the characteristics of these composites improve as the content of OLP increases.The maximum impact strength found is 2.52 KJ/m², and the maximum hardness is 7.24 N/mm², while the compressive strength is around 48.7 MPa. Thermal conductivity decreased on the volumetric fraction of 25%, which is within the range of 0.101 W/m·℃. Based on the analysis of the FTIR results, it can be claimed that the change in intensities and positions of the peaks may be associated with the interaction between the OLP and the polyester matrix. The SEM data suggest that the OLP is dispersed throughout the matrix, and strong interfacial adhesion exists between them. In summary, this work highlights the prospects of using OLP-filled unsaturated polyester composites for several purposes due to the improved mechanical and thermal characteristics.